Essays on economic growth - Ribeiro, Marcos Júnio (2024)
This doctoral dissertation comprises three independent papers focusing on economic growth. The first paper investigates the impact of foreign direct investment (FDI), specifically through greenfield and mergers and acquisitions, on Brazilian economic growth. Findings reveal that while FDI alone does not significantly influence Brazilian growth, its positive effects are enhanced by local conditions. Notably, FDI via greenfield positively impacts Brazilian growth, while the effects of FDI through mergers and acquisitions and FDI volatility are negligible. The second paper explores the misallocation of talent in the Brazilian labor market, particularly among teachers, and its adverse effects on the workforce and economic development. Barriers in the labor and education markets lead to talent misallocation, hindering economic growth. Eliminating these barriers could result in a substantial 16.94% increase in Brazilian income. The third paper examines the spillover effects of intermediate goods on income per worker, using a general equilibrium model with four sectors: agriculture, industry, traditional services, and modern services sectors. The study demonstrates that closing the productivity gap in the industry has a more significant average impact on GDP per worker and aggregate productivity compared to other sectors. Furthermore, in countries with highly efficient agricultural and industrial sectors, a structural change favoring the services sector, without a necessary increase in productivity, exacerbates the gap in GDP per worker between countries.